2020
DOI: 10.24170/17-2-4141
|View full text |Cite
|
Sign up to set email alerts
|

The year in cardiology: acute coronary syndromes

Abstract: Volume 17 Number 2 patients with STEMI, and, indeed, is a prognostic marker in these patients (see below). This might be relevant because risk stratification and management are probably different for plaque fissure and erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(51 reference statements)
0
1
0
1
Order By: Relevance
“…The authors confirmed their findings in two validation cohorts. However, when age is incorporated in the algorithm in order to improve the specificity, adding other confounders such as chronic kidney disease, chronic heart failure and atrial fibrillation should also be considered [17]. Twerenbold et al evaluated the real-world performance of the 0 h/1 h algorithm and confirmed its excellent applicability [18].…”
Section: H/1 H Algorithmmentioning
confidence: 99%
“…The authors confirmed their findings in two validation cohorts. However, when age is incorporated in the algorithm in order to improve the specificity, adding other confounders such as chronic kidney disease, chronic heart failure and atrial fibrillation should also be considered [17]. Twerenbold et al evaluated the real-world performance of the 0 h/1 h algorithm and confirmed its excellent applicability [18].…”
Section: H/1 H Algorithmmentioning
confidence: 99%
“…Соответственно, при обсуждении значимости исследования ISAR-REACT 5 мнения разделились. Так, часть специалистов не сочла имеющиеся недостатки критическими и в целом признала практическую ценность его результатов [14][15][16], в то время как другие указывают на недостаточную убедительность полученных данных [17,18].…”
Section: прямое сопоставление прасугрела и тикагрелора при раннем инвunclassified